Apologetyka Teodoreta z Cyru wobec filozofii Platona - Karas, Marcin (Vox Patrum, 2002)
The considerations allow us to say that ancient literature (even in philosophical sphere) was important for the Church writers not only by its rhetorical function, but also by the historical one to give a full and complete view of ancient culture as well as various myths and superstitions accepted by well educated pagan groups of the late Roman Empire. The discussed questions should be more particularly analyzed using Greek-language editions and modem historical literature. The works of Theodoret can also answer other questions raised by historians.